Ultrasonic material characterization using diffraction-free PVDF receivers - Adamowski, Julio C.; Buiochi, Flávio; Higuti, Ricardo T. [UNESP] (Elsevier, 2010)
This work describes the use of a large aperture PVDF receiver in the measurement of density of liquids and elastic constants of composite materials. The density measurement of several liquids is obtained with the accuracy of less than 0.2% using a conventional NDT emitter transducer and a 70-mm diameter, 52-μm P(VDF-TrFE) membrane with gold electrodes. The determination of the elastic constants of composite materials is based in the measurement of phase velocity. It is shown that the diffraction can lead to errors around 1% in the velocity measurement when using a pair of ultrasonic transducers (1MHz and 19mm diameter) operating in transmission-reception mode separated by a distance of 100 mm. This effect is negligible when using a pair of 10-MHz transducers. On the other hand, the dispersion at 10 MHz can result in errors of about 0.5%, measuring the velocity in composite materials. The use of an 80-mm diameter, 52-μm thick PVDF membrane receiver allows measuring the phase velocity without the diffraction effects.
Keywords: Density; Diffraction-free receiver; Elastic constant; Material characterization; PVDF; Density Measurements; Diffraction effects; Gold electrodes; Large aperture; Material characterizations; PVDF membrane; Reception modes; Composite materials; Composite micromechanics; Elastic constants; Intensive care units; Measurement errors; Phase velocity; Transducers; Ultrasonic transducers; Ultrasonics; Velocity; Velocity measurement; Density of liquids